Caiçara: leprosy in women’s destinations (Research, Society and Development, 2020)
The present article refers to the history of leprosy in Brazil observed from a Brazilian film from 1950, the golden period of the isolation of lepers in the country and in the world. The story of an era caught in an artistic-cultural piece produced for entertainment, where behaviors and mentalities that led to the sanitary exile of lepers in Brazil are unveiled. To understand both the film and its plot, we sought to articulate and combine recent research on leprosy in Brazil and the world with feminist studies, with the aim of clarifying the central character that is a young woman, the daughter of isolated lepers, and directly affected by the scourge that devastated his family. The research then aimed to understand the history of leprosy from a source hitherto underutilized by historians and other scholars on the subject. It was a qualitative, exploratory, bibliographic and documentary research carried out in primary and secondary sources, in addition to the film itself, which sought to articulate the history of leprosy with research on feminism. It was concluded that leprosy during most of the twentieth century instilled a collective fear incompatible with its real dangerousness, however, understandable in light of its long history of discrimination fueled by religious and cultural prejudices since the ancient world. In short, a time when leprosy was filled with fears and taboos that were understandable only in the light of its long history. A time when the current hansen's disease did not yet exist, as it was in gestation.